Dinamaiya Shawl / Dinie Qadeja Zulkurnain ... [et al.]. - Zulkurnain, Dinie Qadeja; Abdul Halim, Siti Norhumaira; Mohd Jailani, Nor Aina Sahira; Ismail, Nur Atiqah Farhana (2021)
We are starting our own business as partners and deciding to call our business as Dinamaiya Shawl Boutique. Dinamaiya shawl located at Taman Tun Dr Ismail in Kuala Lumpur. Our main activity of business is selling high quality shawl. Next, our main aims is to fulfill the needs of Muslim women in covering their “Aurah” which following the “Syarak” in Islam and also look beautiful at the same time by wearing shawl with their own way to styling it. It reflects on how they could wear them neatly and fashionably. Scarves are really important in the society in nowadays.